Cancer incidence and mortality in England and Wales : trends and risk factors - Swerdlow, Anthony (Oxford medical publications., 2001)
This volume presents new analyses that bring together data in cancer trends in the country since 1868. Detailed consideration is given to the reasons for changes in rates of cancer, in relation to a wide range of risk factors and preventive factors.